2021
DOI: 10.1049/bme2.12032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of facial tattoos and paintings on face recognition systems

Abstract: In recent years, face recognition technologies have shown impressive recognition performance, mainly due to recent developments in deep convolutional neural networks. Notwithstanding those improvements, several challenges which affect the performance of face recognition systems remain. The authors investigate the impact that facial tattoos and paintings have on current face recognition systems. To this end, they first collected an appropriate database containing image-pairs of individuals with and without faci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In coherence with the findings in [4], it is of interest to make facial analysis systems more robust towards facial tattoos. One way to do this is face completion, where missing or occluded parts of a face are reconstructed; such approaches have, for instance, shown to improve face recognition performance for some occlusions [5].…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…In coherence with the findings in [4], it is of interest to make facial analysis systems more robust towards facial tattoos. One way to do this is face completion, where missing or occluded parts of a face are reconstructed; such approaches have, for instance, shown to improve face recognition performance for some occlusions [5].…”
Section: Introductionmentioning
confidence: 75%
“…The database used by the authors includes different types of disguises including facial paintings. Coherent with these findings, Ibsen et al showed in [4] that facial tattoos and paintings can severely affect different modules of a face recognition system including face detection as well as feature extraction and comparison.…”
Section: B Facial Alterationsmentioning
confidence: 96%
See 3 more Smart Citations